Análisis financiero y plan de mercadeo para la comercialización del dispositivo ClickShare para la empresa DMS - Delgado-Valverde, Iván; Solís-Zúñiga, German; Umaña-Sánchez, Roy; Villalobos Camacho, Mariángel (Instituto Tecnológico de Costa Rica, 2018)
Digital Management Systems (DMS) is a Costa Rican company dedicated to the commercialization of integrated security and access control systems. As part of its product portfolio, the Company added ClickShare, an artifact intended to improve simultaneous content sharing by two or more users, all from their own mobile devices. Despite its success in Europe, sales in Costa Rica have not been as expected. Therefore, the current challenge is to identify how to sell the product from a marketing perspective in order to increase sales while achieving financial goals. This qualitative research was conducted to address this problem by diagnosing the product’s current situation, using different tools such as Porter’s model, a Cause and Effect Analysis and a marketing research where 45 managers were interviewed. This research found that 76% of interviewed potential buyers have a need for simultaneously content sharing in enterprises and that the products these companies are using do not meet ClickShare’s value proposition. The marketing plan is made to define strategies and policies aligned with the company's mission and vision in order to increase DMS’s sales. In addition, a financial analysis is carried out that supports the estimated margin to be used considering operative cost, inflation, exchange rate to assure a rate higher than its cost of capital.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2018.
Keywords: Mercados; Investigación; Mercadeo; Análisis; ClickShare